1996
DOI: 10.1557/jmr.1996.0280
|View full text |Cite
|
Sign up to set email alerts
|

Electronic bonding characteristics of hydrogen in bcc iron: Part I. Interstitials

Abstract: Electronic structure calculations were carried out for bcc iron (Fe) clusters with or without hydrogen (H), and also involving a vacancy, using the self-consistent Discrete Variational method (DV-Xa) within the local density functional formalism. Bonding characteristics investigated show the following: (i) Interstitial H notably decreases interatomic Fe-Fe bond strengths, but acts over a small distance (within 0.3 nm).(ii) In the perfect Fe lattice field, interstitial H feels a repulsive force at any site. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 19 publications
2
21
0
2
Order By: Relevance
“…The advantage of this approach is its transparency and simplicity which, for example, allows one to avoid the convergence problem associated with the Hartree-Fock or Density Functional Theory (DFT) methods. This EHT study is closely related to the recent ab initio calculation of the H 2 adsorption on a 32-atom cluster [5].…”
Section: Introductionsupporting
confidence: 53%
“…The advantage of this approach is its transparency and simplicity which, for example, allows one to avoid the convergence problem associated with the Hartree-Fock or Density Functional Theory (DFT) methods. This EHT study is closely related to the recent ab initio calculation of the H 2 adsorption on a 32-atom cluster [5].…”
Section: Introductionsupporting
confidence: 53%
“…Itsumi et al carried out electronic structure calculations for body-centered cubic (bcc) Fe with interstitial H by using the first-principles discrete variational method. [80] They reported that the volume expansion is to be expected and the Fe-H interaction occurs mainly via the Fe 4s and H 1s orbitals. A charge transfer of ∼ 0.6e from Fe to H leads to a decrease in the metallic bond strength.…”
Section: Interstitial Effect On Magnetic Properties and Magnetic Entrmentioning
confidence: 98%
“…Cette modification de la structure électronique locale des atomes de métal, combinée à une augmentation de la distance interatomique, affecte directement les forces de cohésion du réseau. Dans le cas des métaux de transition tels que le fer, cet effet se traduit par une diminution des forces de cohésion [4].…”
Section: Données Physiquesunclassified
“…L'absorption d'hydrogène conduit à un affaiblissement des liaisons métal-métal par modification de l'environnement électronique des atomes [4,[60][61][62]. Ce phénomène, qui est à l'origine de l'effet fragilisant de l'hydrogène, est d'autant plus marqué que la concentration locale en hydrogène est grande.…”
Section: Décohésion Associée Aux Interactions éLectroniques Hydrogèneunclassified